Isolation of poly[d-lactate (LA)-co-3-hydroxybutyrate)]-degrading bacteria from soil and characterization of d-LA homo-oligomer degradation by the isolated strains. (September 2020) - Hori, Chiaki; Sugiyama, Tomohiro; Watanabe, Kodai; Sun, Jian; Kamada, Yuu; Ooi, Toshihiko; Isono, Takuya; Satoh, Toshifumi; Sato, Shin-ichiro; Taguchi, Seiichi; Matsumoto, Ken'ichiro
Abstract: P[d -lactate (LA)- co -3-hydroxybutyrate (3HB)] is an artificial polyhydroxyalkanoate (PHA) containing unusual d -LA units. In this study, the P(d -LA- co -3HB)-degrading bacterial group in the soil was analyzed and the bacterial degradation of the d -LA clustering structure in the copolymer were evaluated by using chemically synthetic d -LA homo-oligomers. A total of 216 soil samples were screened on the basis of clear zone formation on agar plates containing emulsified P(64 mol% d -LA- co -3HB). The 16S rRNA analysis of the isolated bacteria resulted in the identification of eight Variovorax, three Acidovorax, and one Burkholderia strains, which are closely related to previously identified natural PHA-degrading bacteria. These bacteria nearly consumed the P(d -LA- co -3HB) emulsion in the liquid culture; however, a small amount of the d -LA fraction remained unconsumed, which should be attributable to the d -LA-clustering structure in the copolymer. Cultivation of the isolated bacteria with the d -LA homo-oligomers revealed that the oligomers with a degree of polymerization (DP) ranging from 10 to 30 were partly consumed by six Variovorax and one Acidovorax strains. In contrast, the oligomers with DP ranging from 20 to 60 were not consumed by the isolated bacteria. These results indicate that d -LA homo-oligomers with DP higher than approximately 20 are hardly degraded by the soil bacteria. Molecular dynamic simulation of the d -LA homo-oligomers indicated that the upper limit of DP is likely to be determined by the conformational structure of the oligomers in water. The information obtained in this study will be useful for the molecular design of biodegradable d -LA-containing polymers. Highlights: 11 P(d -lactate- co -3-hydroxybutyrate)-degrading soil bacteria were isolated. d -LA homo-oligomers with approx. DP ≥ 20 were not consumed by the isolates. The conformations of d -LA homo-oligomers were estimated by MD simulation.